2020
DOI: 10.1097/md.0000000000021076
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of ultrasound-guided needle biopsy in undiagnosed pleural effusions

Abstract: Background and Objective: Undiagnosed pleural effusions (UPEs) are a common problem of respiratory medicine, leading to an increased diagnostic burden globally. However, the most efficient and cost-effective approaches to UPEs remain controversial. This study aimed to assess the diagnostic value of ultrasound-guided needle biopsy (UGNB) in UPEs. Methods: We conducted a search of PubMed, Embase, the Cochrane Library and reference lists of retrieved studies with no public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…The literature comparing ultrasound-guided to CT-guided biopsies is sparse. A recent meta-analysis across seven studies and 165 patients with US-guided pleural biopsies across both cutting needles and reverse-bevel needles suggested a pooled sensitivity of 83% (95% CI 75-89%) with rates of pneumothorax at 3.6%, wound infection 3%, and empyema < 1% [65]. This is similar to the sensitivity suggested by Metintas et al for their CT-guided Abrams needle technique.…”
Section: Ultrasound Vs Ct-guidedsupporting
confidence: 61%
“…The literature comparing ultrasound-guided to CT-guided biopsies is sparse. A recent meta-analysis across seven studies and 165 patients with US-guided pleural biopsies across both cutting needles and reverse-bevel needles suggested a pooled sensitivity of 83% (95% CI 75-89%) with rates of pneumothorax at 3.6%, wound infection 3%, and empyema < 1% [65]. This is similar to the sensitivity suggested by Metintas et al for their CT-guided Abrams needle technique.…”
Section: Ultrasound Vs Ct-guidedsupporting
confidence: 61%
“…In pleural tumors, a biopsy is usually necessary so that histologic diagnosis and appropriate therapy can be initiated. Ultrasound-guided biopsy has a very high diagnostic accuracy and a low complication rate [49], as a puncture route can be chosen to avoid the interposition of ribs and intercostal vessels. It is best to biopsy a parietal pleural lesion at a site where pleural effusion is present to reduce the risk of pneumothorax (▶ Fig.…”
Section: Solid Pleural Lesions and Subpleural Parenchymal Changes (Di...mentioning
confidence: 99%
“…The Abrams and Tru-Cut biopsy needles are the most commonly used devices for closed pleural biopsy. [15,16] The Abrams needle [Fig. 3] consists of 3 individual components: 2 concentric tubes and a stylet.…”
Section: Biopsy Needlesmentioning
confidence: 99%
“…Recently, a systematic review and metanalysis reported that direct USguided closed pleural biopsy had a pooled sensitivity and specificity for undiagnosed exudates of 83% and 100%, respectively. [16] Alternatively, "ultrasound-assistance" describes a free-hand technique in which the pleural target is marked on the skin after noting the angle, depth, and location of the diaphragm and neurovascular bundle. The procedure is then performed during a breath hold without changing the patient's position.…”
Section: Ultrasound Guidancementioning
confidence: 99%
See 1 more Smart Citation